2019
DOI: 10.3389/fimmu.2018.03014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Associated Long Non-coding RNA Transcription and Gene Regulation in Experimental Models of Rickettsial Infection

Abstract: Recent discovery that much of the mammalian genome does not encode protein-coding genes (PCGs) has brought widespread attention to long noncoding RNAs (lncRNAs) as a novel layer of biological regulation. Enhancer lnc (elnc) RNAs from the enhancer regions of the genome carry the capacity to regulate PCGs in cis or in trans. Spotted fever rickettsioses represent the consequence of host infection with Gram-negative, obligate intracellular bacteria in the Genus Rickettsia. Despite being implicated in the pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The quantity and quality of enriched total RNA was ascertained, respectively, on a Multiskan TM Go Spectrophotometer (Thermo Fisher Scientific) and Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA), and only RNA samples with an RNA integrity number (RIN) of >9 were included in our experiments. The enriched RNA was subjected to reverse transcription, followed by preparation of barcoded and strand-specific complementary DNA (cDNA) libraries using TruSeq RNA Sample Prep Kit (Illumina), as described earlier [30]. The cDNA libraries were then processed for sequencing as 50-base-long paired-end reads on an Illumina HiSeq 1500 at the Next Generation Sequencing core facility of the UTMB.…”
Section: Methodsmentioning
confidence: 99%
“…The quantity and quality of enriched total RNA was ascertained, respectively, on a Multiskan TM Go Spectrophotometer (Thermo Fisher Scientific) and Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA), and only RNA samples with an RNA integrity number (RIN) of >9 were included in our experiments. The enriched RNA was subjected to reverse transcription, followed by preparation of barcoded and strand-specific complementary DNA (cDNA) libraries using TruSeq RNA Sample Prep Kit (Illumina), as described earlier [30]. The cDNA libraries were then processed for sequencing as 50-base-long paired-end reads on an Illumina HiSeq 1500 at the Next Generation Sequencing core facility of the UTMB.…”
Section: Methodsmentioning
confidence: 99%
“…Chowdhury and colleagues provided the very first experimental evidence suggesting altered expression of pulmonary host cell ncRNAs and their involvement in the host defense response (Chowdhury et al, 2019). The profiling of the expression of host lung cell lncRNAs during infection of mice with R. conorii, simulating the pathogenesis of human spotted fever rickettsioses (Fig.…”
Section: Rickettsiamentioning
confidence: 99%
“…Additional in-depth analyses concluded that the genomic loci of NONMMUT013718 and NONMMUT024103 might regulate the expression of nearby protein-coding genes (PCGs), namely inhibitor of DNA binding 2 (Id2) and apolipoprotein 10b (Apol10b), respectively (Chowdhury et al, 2019). The regulatory role of these elncRNAs was confirmed during R. conorii infection in vitro, with induced expression of NONMMUT013718 (Id2) in murine macrophages and NONMMUT024103 (Apol10b) in endothelial cells clearly visible (Chowdhury et al, 2019). As expected, shRNAmediated knockdown of both elncRNAs reduced the expression of their endogenous target PCGs.…”
Section: Rickettsiamentioning
confidence: 99%
See 2 more Smart Citations